Natural regeneration of wetlands under climate change - Zivec, Peta; Sheldon, Fran; Capon, Samantha J. (Frontiers in Environmental Science, 2023)
Wetlands are increasingly valuable under climate change in terms of their ecological functions, ecosystem services and biodiversity. Simultaneously, wetlands are hotspots for anthropogenic activity due to their high soil fertility and water supply, and have been subject to significant modification, degradation and staggering losses. With climate change having increasing impacts on ecosystems globally, the need for wetland restoration is rapidly growing. Natural regeneration, whereby vegetation is allowed to regrow via propagules already present within the landscape, provides a cost-effective and large-scale approach to restoration for many, but not, all wetlands. This paper emphasises the importance of natural regeneration of wetland ecosystems as an effective restoration approach under climate change. We discuss drivers and barriers of natural regeneration of wetlands under climate change along with implications for management approaches. Drivers of wetland natural regeneration are depicted along with their interactions, displaying a range of abiotic and biotic factors that influence ecosystem change. Key adaption approaches to maintain and promote natural regeneration of wetlands under climate change include integrated land and water management, protecting and promoting key relevant biotic and abiotic processes within landscapes, and reconsidering current weed management strategies. Most importantly, however, natural regeneration should be recognised as an important and viable restoration approach under climate change in order to meet restoration demand and promote landscape resilience to changing conditions.